A 1-week extension of a ketogenic diet provides a further decrease in myocardial (18)F-FDG uptake and a high detectability of myocarditis with FDG-PET - Clément, Alexandra (J Nucl Cardiol, 2018)
BACKGROUND: Short periods of fasting and/or low-carbohydrate diet have been proven beneficial for decreasing the myocardial uptake of (18)F-fluorodeoxyglucose ((18)F-FDG) and enhancing the detection of inflammatory heart diseases by (18)F-FDG positron emission tomography (PET). This study aimed at determining whether this benefit is increased when a low-carbohydrate ketogenic diet is prolonged up to 7 days. METHODS: Wistar rats underwent serial (18)F-FDG-PET imaging after an 18-hour fasting period and after 2, 4 and 7 days of a ketogenic diet (3% carbohydrate) and they were compared to rats submitted to the same protocol but with normal diet (44% carbohydrate). The (18)F-FDG-PET/ketogenic protocol was also applied in rats with immune myocarditis (injection of porcine cardiac myosin). RESULTS: The 7-day ketogenic diet was associated with (1) a sustained increase in circulating ketone bodies at an equivalent level to that reached after 18-hour fasting, (2) a gradual decrease in (18)F-FDG uptake within normal myocardium reaching a lower level compared to fasting at the 7th day (myocardium-to-blood ratios: 1.68 ± 1.02 vs 3.25 ± 1.40, P < .05) and (3) a high (18)F-FDG-PET detectability of myocarditis areas. CONCLUSION: One-week extension of a ketogenic diet provides a further decrease in the (18)F-FDG uptake of normal myocardium and a high detectability of inflammatory areas. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12350-018-1404-7) contains supplementary material, which is available to authorized users.